Dimensi Etis Taoisme dan Manfaatnya bagi Pembangunan Berwawasan Lingkungan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Taoism is one of Chinese Philosophical Schools which emphasizes more on individual interest than social interest. The ethic of Taoism suggest the harmony life by the nature. It is able to become a foundation of eco-development. The main teaching of Taoism is Tao, Te and Wu-wei. Taoism comprises metaphysical concept of being and ending of something. Tao realizing of thing is called Te. Te comprises goodness or wisdom must be done by human being to unite with Tao. Wu-wei is non-action which is not suitable with the nature of nature. The main teaching of Taoism is creating harmony life between human being and the nature. The object of this research is Taoism philosophy. The method used in this research is hermeneutics, consisting of description, holistics, critical reflection and idealization. Description is used to understand the value of Taoism. Holistics is used to see the ethics of Taoism wholely in order to get the essence of relation between human being and the nature. Critical reflection has function to gain new comprehension on ethical Taoism and ecodevelopment. Idealization is used to comprehend deeply and purely on the ethics of Taoism. The result of this research shows that the ethic of Taoism containing the balance and harmony of human life and the nature. It can be used to lead the eco-development.